A Systems Analysis of Fluoride Varnish Application in General Dental Practice in Scotland using the Functional Resonance Analysis Method - Ross, Alastair; Kidd, Jamie; Gnich, Wendy; Sherriff, Andrea; Deas, Leigh; Rhouma, Ousama; Macpherson, Lorna (Caries Research, 2017)
Under Scotland’s child oral health improvement programme (Childsmile) programme dental practices delivering National Health Service (NHS) care are expected to apply sodium fluoride varnish to the teeth of all children at six-monthly intervals from the age of two years. Despite some recognised programme success this key preventive intervention is still variable. Aim: This organisational-level project aimed to study the work system around fluoride varnish application in the practice setting, to identify mechanisms and contextual factors likely to come into play in complex interventions to increase application rates. The methodology involved applying the Functional Resonance Analysis Method to synthesise multiple data sources, including: a longitudinal survey of GDPs (n = 1,090; 65% follow up rate); in-depth interviews with practitioners and public health experts (n = 43); ‘World Café’ (4) workshop activities with Childsmile staff (n = 56); and NHS rouDownloaded by: Glasgow Univ.Lib. 130.209.6.42 - 11/2/2017 11:15:27 AM Abstracts: 64th ORCA Congress Caries Res 2017;51:290–385 DOI:10.1159/000471777 367 tine varnish claims data for 2015/16 (n = 86,726 claims at 807 Practices). Results Various crosslinked areas affecting varnish application were identified: priorities of care and preventive culture; practice management including time, space and use of the dental team; parental wishes and child compliance; risk and efficacy evidence; and issues with regards to the NHS remuneration system. Conclusion This study identified a number of interlinked organisationlevel issues around fluoride varnish application in general dental practice. These have been developed into a randomised pilot and feasibility study which is now underway, involving an enhanced audit and feedback intervention.